Does the novel artificial cervical joint complex resolve the conflict between stability and mobility after anterior cervical surgery? a finite element study - Meng, Bing; Zhao, Xiong; Wang, Xin-Li; Wang, Jian; Xu, Chao; Lei, Wei (Frontiers in Bioengineering and Biotechnology, 2024)
Background and objective: Our group has developed a novel artificial cervical joint complex (ACJC) as a motion preservation instrument for cervical corpectomy procedures. Through finite element analysis (FEA), this study aims to assess this prosthesis's mobility and stability in the context of physiological reconstruction of the cervical spine.A finite element (FE) model of the subaxial cervical spine (C3-C7) was established and validated. ACJC arthroplasty, anterior cervical corpectomy and fusion (ACCF), and two-level cervical disc arthroplasty (CDA) were performed at C4-C6. Range of motion (ROM), intervertebral disc pressure (IDP), facet joint stress (FJS), and maximum von Mises stress on the prosthesis and vertebrae during loading were compared.Compared to the intact model, the ROM in all three surgical groups demonstrated a decline, with the ACCF group exhibiting the most significant mobility loss, and the highest compensatory motion in adjacent segments. ACJC and artificial cervical disc prosthesis (ACDP) wellpreserved cervical mobility. In the ACCF model, IDP and FJS in adjacent segments increased notably, whereas the index segments experienced the most significant FJS elevation in the CDA model. The ROM, IDP, and FJS in both index and adjacent segments of the ACJC model were intermediate between the other two. Stress distribution of ACCF instruments and ACJC prosthesis during the loading process was more dispersed, resulting in less impact on the adjacent vertebrae than in the CDA model.The biomechanical properties of the novel ACJC were comparable to the ACCF in constructing postoperative stability and equally preserved physiological mobility of the cervical spine as CDA without much impact on adjacent segments and facet joints. Thus, the novel ACJC effectively balanced postoperative stability with cervical motion preservation.